Toll-Like Receptors Represent an Important Link for Sex Differences in Cardiovascular Aging and Diseases - Echem, Cinthya; Akamine, Eliana H. (Frontiers in Aging, 2021)
Human life span expectancy has increased, and aging affects the organism in several ways, leading, for example, to an increased risk of cardiovascular diseases. Age-adjusted prevalence of the cardiovascular diseases is higher in males than females. Aging also affects the gonadal sex hormones and the sex differences observed in cardiovascular diseases may be therefore impacted. Hormonal changes associated with aging may also affect the immune system and the immune response is sexually different. The immune system plays a role in the pathogenesis of cardiovascular diseases. In this context, toll-like receptors (TLRs) are a family of pattern recognition receptors of the immune system whose activation induces the synthesis of pro-inflammatory molecules. They are expressed throughout the cardiovascular system and their activation has been widely described in cardiovascular diseases. Some recent evidence demonstrates that there are sex differences associated with TLR responses and that these receptors may be affected by sex hormones and their receptors, suggesting that TLRs may contribute to the sex differences observed in cardiovascular diseases. Recent evidence also shows that sex differences of TLRs in cardiovascular system persists with aging, which may represent a new paradigm about the mechanisms that contribute to the sex differences in cardiovascular aging. Therefore, in this mini review we described the latest findings regarding the sex differences of TLRs and associated signaling in cardiovascular diseases during aging.